2019
DOI: 10.1111/ijcp.13349
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis and effectiveness of pharmacist‐managed outpatient clinics in Helicobacter pylori eradication therapy

Abstract: Background Helicobacter pylori is involved in many upper gastrointestinal diseases such as peptic ulcers and gastric cancers. In this study, we compared the cost‐effectiveness of lansoprazole and vonoprazan in H. pylori eradication therapy and examined the effectiveness of pharmacist‐managed outpatient clinics. Methods We investigated the efficacy and cost‐effectiveness of pharmacist‐managed outpatient clinics in H. pylori eradication therapy at our hospital from January 2015 to December 2017. The subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Pharmacist‐managed clinics (PMCs) provide outpatient services such as medication therapy management (MTM), disease management and patient education 1 . Previous studies have shown that implementing MTM has a significant impact on enhancing medication adherence, improving clinical outcomes 2–9 and achieving cost‐effectiveness 10–14 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Pharmacist‐managed clinics (PMCs) provide outpatient services such as medication therapy management (MTM), disease management and patient education 1 . Previous studies have shown that implementing MTM has a significant impact on enhancing medication adherence, improving clinical outcomes 2–9 and achieving cost‐effectiveness 10–14 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…72 In Japan, a study looked at an enhanced compliance program by getting pharmacists to provide instruction for patients being prescribed eradication therapy but found modest, if any, benefit with 91% achievement in the intervention group compared to 88% in the group getting vonoprazan without special pharmacist instruction with a slight benefit in cost-effectiveness ratio (223 vs 224). 73 A study in Israel looked at educational interventions for primary care physicians and found that a program including distribution of printed materials, educational outreach visits, and education over a social media platform improved adherence to guidelines significantly. 74 In China, it was shown that sending patients short phone text messages could increase compliance and improve adherence to therapy.…”
Section: Adheren Cementioning
confidence: 99%
“…Prior studies evaluating pharmacists’ involvement with H pylori have primarily focused on the impact of medication counseling and adherence interventions. 8-11 Ravnan et al 8 highlighted that a telephone-based clinic, in which pharmacists evaluated the appropriateness of H pylori treatment via prescriptions and provided counseling for 42 patients, led to 100% treatment adherence with minimal adverse effects and no significant drug interactions. Al-Eidan et al 10 assessed the impact of providing counseling and 1 week of lansoprazole, amoxicillin, and clarithromycin from the hospital pharmacy (n = 38) versus standard of care (n = 38).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 89% of patients in the intervention group versus 67% in the control group took >90% of medications ( P < 0.01). 11 Seko et al 9 determined the eradication rate and cost-effectiveness of pharmacists prescribing amoxicillin + clarithromycin or metronidazole + lansoprazole or vonoprazan. Eradication rates were higher in patients who received counseling from the pharmacist (91.4% vs 75.2%, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation